The hydrolase LpqI primes mycobacterial peptidoglycan recycling - Patrick J. Moynihan (Nature Portfolio, 2019)
Bacterial growth and division require remodelling of the cell wall, which generates free peptidoglycan fragments. Here, Moynihan et al. show that Mycobacterium tuberculosis can recycle components of their peptidoglycan, and characterise a crucial enzyme required for this process.